Precedentes e fontes do direito : uma perspectiva da dogmática jurídica - Camatta, Roberto Mielke (2016)
The present dissertation means to analyse the “precedents” by the study of dogmatic and semantic construtivism-logical. Thereon, perceiving such institute and proposing at the end a method of incidence of the precedents, once that it is common to have problems in its application, mostly in the moment of the selection of its integrating elements – ratio decidendi and the facts. To do this article one will use the synthetic scientific method and the research it will be made by specialized bibliography.